Introduction: Radical Teaching About Human Rights Part II - Bennett, Michael; O'Malley, Susan (Radical Teacher, 2016)
In our introduction to the first of these two issues of Radical Teacher devoted to “Radical Teaching About Human Rights,” we cautioned that all forms of Human Rights Education (HRE) are not radical. The problem, we pointed out, with rights discourse is that it can mask the politics of how rights are defined, whose rights are recognized, and how they are enforced. This problem becomes evident when HRE is bound up with a neoliberal, or worse than neoliberal, perspective that points fingers at others and rallies troops for supposedly humanitarian interventions while eliding the role of the United States as an imperializing settler colonial state. Fortunately, we have once again received several essays that seem to us to be aware of this danger and provide admirable examples of radical teaching about human rights.